2020
DOI: 10.1111/sms.13776
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine increases strength and power performance in resistance‐trained females during early follicular phase

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 41 publications
(135 reference statements)
4
45
0
Order By: Relevance
“…In the primary search, there was a total of 1214 results; 1184 documents were excluded after reading the title or abstract ( Figure 1 ). After reading 30 full-text papers, 7 studies were found that satisfied the inclusion criteria [ 7 , 10 , 11 , 15 , 16 , 17 , 18 ]. In the secondary search, there were 669 search results, and one study was additionally included [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the primary search, there was a total of 1214 results; 1184 documents were excluded after reading the title or abstract ( Figure 1 ). After reading 30 full-text papers, 7 studies were found that satisfied the inclusion criteria [ 7 , 10 , 11 , 15 , 16 , 17 , 18 ]. In the secondary search, there were 669 search results, and one study was additionally included [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the secondary search, there were 669 search results, and one study was additionally included [ 19 ]. Therefore, we included a total of 8 studies in the present review [ 7 , 10 , 11 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations